Africa-Europe: the population inversion - (:unkn) unknown (My University, 2013)
To understand the demographics of Africa as a whole or of its sub-Saharan part, put into perspective with that of Europe is éclaicant using data supplied by the international databases. However, before commenting on the results then analyzed in a prospective mind, it is important to show some humility given the fact that a number of demo-graphic data for Africa are estimates only.
Keywords: African Research